1999
DOI: 10.1111/j.1751-0813.1999.tb11712.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a competitive inhibition ELISA and the card agglutination test for detection of antibodies to Anaplasma marginale and Anaplasma centrale in cattle

Abstract: We conclude that the competitive inhibition ELISA is a useful alternative to the card agglutination test for detection of A marginale or A centrale infection in cattle. The assay should be particularly useful for epidemiological applications such as prevalence studies and control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
2
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 5 publications
0
28
2
2
Order By: Relevance
“…10,17,23,26,28,31 To the authors' knowledge, this is the first attempt at estimating accuracy of these tests using a Bayesian latent class approach. The MSP-5 cELISA had the highest accuracy of the 3 evaluated tests based on the dichotomous interpretation with a Youden index of 0.88.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…10,17,23,26,28,31 To the authors' knowledge, this is the first attempt at estimating accuracy of these tests using a Bayesian latent class approach. The MSP-5 cELISA had the highest accuracy of the 3 evaluated tests based on the dichotomous interpretation with a Youden index of 0.88.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy of the card test, MSP-5 cELISA, and qPCR were estimated in a latent class analysis using a Bayesian framework (evaluation of direct smears were excluded because of few positive tests). Prior probability distributions for this analysis (Table 1) were based on published literature 26,31 and modified by expert opinion because previous studies employed different reference standards. A 3-test, single population model was used assuming conditional independence between pairs of diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The IFA test, which did not discriminate between Anaplasma species because of antigenic similarity (Palmer, 1989 andVisser et al, 1992) were widely used for serodiagnosis of anaplasmosis (Goff et al, 1985, Montenegro-James et al, 1985and Shkap et al, 1990. A commercial cELISA based on the MSP 5 surface protein has been developed for detection of antibodies against A. marginale (Knowles et al, 1996 andTorioni de Echaide et al, 1998) but, similarly to the IFA, it was found not to be applicable for discrimination between A. centrale-specific antibodies (Molloy et al, 1999 andDe la Fuente et al, 2005). The IFA based on 80 kDa A. centrale antigen differentiated between A. marginale and A. centrale in patent infections only, while the cELISA based on 116 kDa antigen was highly sensitive and specific in carrier infections (Molloy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%